Exploring The Challenges Encountered by Students to Speak English at MA Guppi Sapakeke - Anita, Nur; Hasriani, Hasriani; Fauzan, Muhammad Miftah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This research aims to identify the elements that contribute to students' difficulties speaking English in class as well as the difficulties they face in doing so. This research uses a qualitative descriptive approach in the form of a case study format approach. This information is collected through observation and semi-formal interviews. The participants were class 12 students of MA Guppi Sapakeke. For this research, researcher used ten students as samples. Students face challenges in speaking English in class due to lack of grammar, lack of vocabulary, poor pronunciation, and nervousness. These problems contribute to poor understanding and anxiety, and are exacerbated by the fear of making mistakes and being laughed at. Factors contributing to these challenges include limited opportunities for independent study, lack of motivation to increase vocabulary, and lack of prior English language learning. Furthermore fear of making mistakes and being laughed at also contributes to anxiety.Keywords: Exploring, Challenges, Speaking